2008
DOI: 10.1186/1742-2094-5-35
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1-deficient mice show reduced neuroinflammatory responses and increased peripheral inflammatory responses to peripheral endotoxin insult

Abstract: Background: An endotoxin insult mimics a severe peripheral infection and recent evidence suggests that a single exposure can cause long-term cognitive deficits. A peripheral injection of LPS results in production of pro-inflammatory cytokines, such as IL-1β and TNF-α, in the brain and periphery and these cytokines mediate many effects of the acute phase response including activation of the HPA axis. The chemokine MCP-1 is highly expressed during endotoxemia and although much is known about the importance of MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
64
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 49 publications
8
64
0
1
Order By: Relevance
“…The bacterial endotoxin also markedly increased TNF-a in brain. Other studies have indicated decreased brain GSH and glutathione reductase activity, cyclooxygenase-2 expression, lipid peroxidation, impairment in mitochondrial redox activity (Noble et al 2007;Jacewicz et al 2009), as well as increased production of pro-inflammatory cytokines, such as IL-1b and TNF-a, in the brain and periphery (Buttini et al 1997;Fiorucci et al 2002;Thompson et al 2008) after systemic LPS administration in rodents. In LPS-treated mice, the administration of aspartame resulted in further increase in oxidative stress in brain (though not in the liver), suggesting that the latter is more susceptible to the effect of aspartame.…”
Section: Discussionmentioning
confidence: 96%
“…The bacterial endotoxin also markedly increased TNF-a in brain. Other studies have indicated decreased brain GSH and glutathione reductase activity, cyclooxygenase-2 expression, lipid peroxidation, impairment in mitochondrial redox activity (Noble et al 2007;Jacewicz et al 2009), as well as increased production of pro-inflammatory cytokines, such as IL-1b and TNF-a, in the brain and periphery (Buttini et al 1997;Fiorucci et al 2002;Thompson et al 2008) after systemic LPS administration in rodents. In LPS-treated mice, the administration of aspartame resulted in further increase in oxidative stress in brain (though not in the liver), suggesting that the latter is more susceptible to the effect of aspartame.…”
Section: Discussionmentioning
confidence: 96%
“…3A). Based on the chemoattractant properties of the CCR2/CCL2 signaling (Thompson et al, 2008;Mildner et al, 2009), CCR2 upregulation on both microglia and brain macrophages by EE may suggest that EE could make these cells more responsive and more mobile with respect to future eventual injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation with LPS can induce the expression of iNOS, COX-2, pro-inflammatory cytokines and chemokines in microglial cells (Saud et al, 2005;Thompson et al, 2008;Kao et al, 2010;Lu et al, 2010). Several lines of evidence suggest that microglial cells can secrete pro-inflammatory cytokines, such as IL-1β, IL-6, IFNγ and TNF-α, which in turn, can act on these cells in an autocrine manner (Graeber and Streit, Cell viability assay using CCK-8 kit was examined at 24 h following treatment with visnagin (0, 5, 10, 25, 50 and 100 µM).…”
Section: Discussionmentioning
confidence: 99%